Creating a digital home entertainment system with Windows Media Center - Miller, Michael, 1958- (Que, 2006)
A guide to selecting, purchasing, configuring, and using a home theater PC with Windows Media Center, discussing the diverse applications, features, and functions of the onscreen interface and explains how to use the interface to perform a variety of tasks.